Quinoa (Chenopodium quinoa Willd.): Paving the way towards nutraceuticals and value-added products for sustainable development and nutritional security - Sagar M. Chavan; Abhijit Khadatkar; Muzaffar Hasan; Dilshad Ahmad; Vishal Kumar; N.K. Jain (Applied Food Research)
Quinoa (Chenopodium quinoa Willd.) is often referred to as pseudo-cereal grain, possesses high nutritive value than other food grains; high content of various vitamins, minerals, etc.; and also has high compositions of most vital amino acids, particularly lysine. Due to its premises properties and high genetic variability, it is considered a superfood for nutritional security among the rural population. It also has a remarkable balance of vital amino acids. These grains are ignored in wealthy nations and have lost favor because of their coarse texture, despite their many health advantages. In order to investigate this neglected crop, characterize it, and value it for use in food applications, research and development efforts are expanding. From the perspective of nutritional security for rural populations around the world, this review emphasizes the remarkable nutritional, functional, and agronomical qualities of quinoa. Excellent information about the agronomical, functional, and nutritional qualities of quinoa, research gaps, and technical advancements for its production, pre-processing, and post-processing unit activities is also included in this review. Planning innovative research for the effective utilization of these underutilized grains will benefit greatly from this information.